Modeling sediment transport in Qatar: Application for coastal development planning. (11th November 2017) - Yousif, Ruqaiya; Warren, Christopher; Ben‐Hamadou, Radhouan; Husrevoglu, Sinan
ABSTRACT: Hydrodynamics and sediment transport are key physical processes contributing to habitat structure within the marine environment. Coastal development that results in the alteration of these processes (e.g., changing water flushing and/or sedimentation rates) can have detrimental impacts on sensitive systems. This is a current, relevant issue in Qatar as its coastal regions continue to be developed, not only around the capital of Doha, but in many areas around this Arabian Gulf peninsula. The northeastern Qatari coast is comprised of diverse and sensitive flora and fauna such as seagrass and macroalgae meadows, coral reefs and patches, turtles, and dugongs that tolerate harsh environmental conditions. In the near future, this area may see a rise in anthropogenic activity in the form of coastal development projects. These projects will add to existing natural stresses, such as high temperature, high salinity, and low rates of precipitation. Consequently, there is a need to characterize this area and assess the potential impacts that these anthropogenic activities may have on the region. In the present study, a novel sediment transport model is described and used to demonstrate the potential impact of altering hydrodynamics and subsequent sediment transport along the northeastern Qatar nearshore marine environment. The developed models will be tested using potential scenarios of future anthropogenic activities forecasted to take place in the area. The results will show the effects on water and sediment behavior and provide a scientific approach for key stakeholders to make decisions with respect to the management of the considered coastal zone. Furthermore, it provides a tool and framework that can be utilized in environmental impact assessment and associated hydrodynamic studies along other areas of the Qatari coastal zone. Integr Environ Assess Manag 2018;14:240–251. © 2017 SETAC Key Points: Study introduces development of a sediment transport model for Qatar. Environmental impact assessment framework incorporates mass balance hydrodynamic and sediment transport models, and habitat mapping. Case study for remote pristine nearshore marine system in northeastern Qatar is included. Tool for development planners and decision makers aims to address future sustainable coastal development.